MENINGKATKAN KETERAMPILAN MEMBUAT RAK DARI KARDUS PADA ANAK TUNAGRAHITA RINGAN - Asmadi, Mega Iswari, Ardisal (Jurnal Penelitian Pendidikan Khusus, 2013)
This study aims to: 1) Determine the implementation process of learning the skills to make a shelf out of cardboard through training method and 2) to prove the method can improve the training skills to make a shelf out of cardboard for mild mental retardation children class V in SDLB State 35 North Painan. This research was raised by using action research methods class (Classroom Action Research) conducted in collaboration with colleagues. Data were collected through observation and testing techniques, then analyzed qualitatively and quantitatively. The results showed that 1) the process of implementation in improving the skills of making a shelf out of cardboard through training method is done in two cycles. I made eight cycle times and cycle II four meetings. Activities carried out by following the flow of the cycle: planning, implementation, observation and reflection. 2) Learning outcomes: children's ability to make a shelf out of cardboard with increased exercise this method proved: when asessmen children's ability to make a shelf out of cardboard is : AR (63.89%), MR is (52.78%) and RN was (38.89%). I cycle capability AR increased to (86.11%), MR (80.56%) and RN is (75%). Cycle II AR increased to (100%) and MR (94.44%) and RN becomes (91.67%). It can be concluded that the method can improve the skills training makes racks of cardboard mild mental retardation in children in class V SDLB Painan State 35 North. Recommended to teachers in order to use the method in the teaching of other skills training.